Hubungan Dukungan Keluarga Dengan Perilaku Lansia Dalam Pencegahan Hipertensi Di Wilayah Kerja Puskesmas Pasar Ikan Kota Bengkulu Tahun 2025 - Yosi Oktavia; Taufianie Rossita; Hengki Tranado (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The Indonesian Health Survey reported a 29.2% prevalence of hypertension in Indonesia, with 598,983 cases. Among the elderly aged 55-64, the prevalence was 18.7%, 23.8% for those aged 65-74, and 26.1% for those aged 75 and above. The purpose of this study was to determine the relationship between family support and elderly behaviors in preventing hypertension in the Working Area of Pasar Ikan Health Center in Bengkulu City in 2025. The research method used was descriptive research with a cross-sectional approach. The sampling technique used purposive sampling, with a sample size of 64 elderly individuals in the Working Area of Pasar Ikan Health Center in Bengkulu City in 2025. Univariate analysis results showed that the majority of respondents (62.5%) had supportive families and the majority (67.2%) had good behaviors in preventing hypertension. The results of the bivariate chi-square analysis showed a relationship between family support and the behavior of the elderly in preventing hypertension in the Working Area of Pasar Ikan Health Center in Bengkulu City in 2025 (p-value 0.000). There was a correlation between family support and the behavior of the elderly in preventing hypertension in the Working Area of Pasar Ikan Health Center in Bengkulu City in 2025. The results of this study are expected to serve as a reference for respondents to increase their knowledge about the correlation between family support and the behavior of the elderly in preventing hypertension.